2012
DOI: 10.4236/ns.2012.412136
|View full text |Cite
|
Sign up to set email alerts
|

N-Butylpyridoquinoxaline 1,4-dioxide (NBPQD) as a new potent for tumor imaging and therapy

Abstract: The development of new and effective antitumor agents is one of the main goals of medicinal and biochemical research at present. The present study is concerned with the evaluation of the previously synthesized N-Butylpyridoquinoxaline 1,4-dioxide (NBPQD) as an antitumor agent against Ehrlich ascites carcinoma (EAC). The first part of the study (tumor imaging) was to investigate the biodistribution of NBPQD in the organs of EAC-bearing mice using iodine-125 isotope stressing on its distribution in the main orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Total protein levels significantly decreased in tumorbearing animals, which may be explained by enhanced neoplastic cell mitosis, high blood flow and capillary permeability, which allow plasma proteins to escape into the peritoneal cavity, as well as hepatic cell necrosis (16).The nuclear degenerative alterations could be the cause of reduced total protein level that were seen in both the current investigation and previous studies (17). Similarly, Habib et al (18) found that mice carrying EAC had significantly lower levels of total protein and albumin.…”
Section: Discussionmentioning
confidence: 86%
“…Total protein levels significantly decreased in tumorbearing animals, which may be explained by enhanced neoplastic cell mitosis, high blood flow and capillary permeability, which allow plasma proteins to escape into the peritoneal cavity, as well as hepatic cell necrosis (16).The nuclear degenerative alterations could be the cause of reduced total protein level that were seen in both the current investigation and previous studies (17). Similarly, Habib et al (18) found that mice carrying EAC had significantly lower levels of total protein and albumin.…”
Section: Discussionmentioning
confidence: 86%